A COMPREHENSIVE COMPARISON OF VIRTUAL HUMAN RESOURCES EFFECTS BEFORE AND AFTER COVID-19 - M.M. Shaima Hassan Ahmed; M.M. Najah Madad Werdee Kazim (Scholar Express Journals, 2024)
The COVID-19 pandemic played a great and effective role in changing the policies and structures of virtual human resources (VHR) systems of institutions and organizations, whether governmental or private sector. This pandemic has become a wake-up call for these institutions and organizations, as the role of virtual human resources (VHR) has become more important than ever. Human resources specialists are responsible for the health and well-being of employees and must be able to identify and manage risks in addition to their need to be truly aware and able to make communication between employees in order to provide them with a support. What has been mentioned is the basis of human resources structures and their responsibilities and duties towards employees. In this article, a comparative study will be conducted. An analytical study on the importance of virtual human resources before and after the COVID-19 pandemic in three main areas: health and safety, communications and employee support. This study showed after conducting a real survey in one of the institutions affiliated with the Ministry of Higher Education and Scientific Research for ten employees working in human resources as well as another sample of 100 employees who communicate directly with human resources employees
Keywords: COVID-19; virtual human resources; health